Risk of Recurrent Instability After Arthroscopic Stabilization for Shoulder Instability in Adolescent Patients. Issue 9 (17th September 2019) - Kramer, Jonathan; Gajudo, Gio; Pandya, Nirav K.
Background: With the rise of adolescent sports participation, there has been a concomitant increase in not only the incidence but also the treatment of traumatic shoulder instability. Yet, there have been limited data on the failure rates of arthroscopic shoulder stabilization in this population as well as the potential risk factors. Purpose/Hypothesis: The purpose of this study was to determine the failure rates of adolescent patients who underwent arthroscopic labral reconstruction for traumatic anterior shoulder instability. We hypothesized that adolescent failure rates would be significantly higher than what has been reported in the adult population with regard to recurrent instability after surgical intervention. Study Design: Case series; Level of evidence, 4. Methods: This was a retrospective cohort study performed at a single center. Inclusion criteria consisted of all adolescent-aged patients identified who (1) had traumatic anterior shoulder instability, (2) had radiographic findings consistent with anteroinferior capsulolabral injury, and (3) underwent arthroscopic shoulder stabilization. Patient demographics, clinical presentation, imaging, intraoperative findings, and postoperative outcomes were analyzed. Results: A total of 36 patients were identified, with a mean ± SD follow-up of 35.6 ± 13.8 months. The mean patient age at the time of the index procedure was 16.03 ± 1.67 years. All patients underwent arthroscopic shoulder stabilization consisting of arthroscopic Bankart repair. Twelve patients (33.3%) reported either recurrent instability or apprehension, of whom 9 (25.0%) developed recurrent dislocation/subluxation at a mean of 20.67 months postoperatively (range, 16-51 months). No single sport was associated with a statistically significant increased risk of redislocation, although a trend was seen toward those with postoperative participation in high-risk sporting activity. Patients who redislocated their shoulders had a higher frequency of a Hill-Sachs lesion on magnetic resonance imaging (89%) compared with those who did not (52%, P = .048). History of multiple preoperative dislocations, presence of bony Bankart pathology, off-track lesions, and number of anchors utilized were not associated with postoperative dislocation/subluxation. Conclusion: This study demonstrates that adolescent patients treated with arthroscopic shoulder stabilization have a high rate of recurrent instability. The adolescent population may benefit from other stabilization strategies and/or activity modification. Further studies are necessary to determine the reasons for the high rate of redislocation and to develop strategies for prevention.